Transformasi Digital Perbankan Syariah di Indonesia: Peluang dan Tantangan dalam Meningkatkan Inklusi Keuangan Syariah - Rahmadhani, Cahya Afrida; Putri, Juliana (Glossary : Jurnal Ekonomi Syariah, 2025)
Digital transformation has become an essential step in strengthening the competitiveness and outreach of Islamic banking services in Indonesia. Although the number and total assets of Islamic banks continue to grow, their contribution to the overall national banking industry remains relatively small, while the level of Islamic financial literacy and inclusion among the public is still uneven. This situation raises a key question: to what extent can digital transformation enhance Islamic financial inclusion, and what challenges arise in its implementation? This study aims to analyze how digital transformation contributes to improving Islamic financial inclusion in Indonesia and to identify the opportunities and challenges that accompany it, as well as its role in expanding public access to financial services based on sharia principles. Using a qualitative descriptive approach through literature review and analysis of various policies and industry reports, this study examines the opportunities and obstacles in the digitalization of Islamic banking. The findings show that digital transformation creates significant opportunities through the optimization of mobile banking services, Islamic fintech, and integrated digital ecosystems that can reach various layers of society. However, major challenges remain, including low levels of digital and financial literacy, limited technological infrastructure, and the need for stronger regulations and data security. Overall, this study emphasizes that the success of digital transformation in Islamic banking depends greatly on the synergy between industry, regulators, and society in developing a digital financial system that is inclusive, secure, and compliant with sharia principles.